Biotic stress globally downregulates photosynthesis genes - Bilgin, Damla D. (2010)
To determine if damage to foliage by biotic agents, including arthropods, fungi, bacteria and viral pathogens, universally downregulates the expression of genes involved in photosynthesis, we compared transcriptome data from microarray experiments after twenty two different forms of biotic damage on eight different plant species. Transcript levels of photosynthesis light reaction, carbon reduction cycle and pigment synthesis genes decreased regardless of the type of biotic attack. The corresponding upregulation of genes coding for the synthesis of jasmonic acid and those involved in the responses to salicylic acid and ethylene suggest that the downregulation of photosynthesis-related genes was part of a defence response. Analysis of the sub-cellular targeting of co-expressed gene clusters revealed that the transcript levels of 84% of the genes that carry a chloroplast targeting peptide sequence decreased. The majority of these downregulated genes shared common regulatory elements, such as G-box (CACGTG), T-box (ACTTTG) and SORLIP (GCCAC) motifs. Strong convergence in the response of transcription suggests that the universal downregulation of photosynthesis-related gene expression is an adaptive response to biotic attack. We hypothesize that slow turnover of many photosynthetic proteins allows plants to invest resources in immediate defence needs without debilitating near term losses in photosynthetic capacity. © 2010 Blackwell Publishing Ltd.